Bovine coronavirus 5?-proximal genomic acceptor hotspot for discontinuous transcription is 65 nucleotides wide - Wu, Hung-Yi; Ozdarendeli, Aykut; Brian, David A. (My University, 2006)
Coronaviruses are positive-strand, RNA-dependent RNA polymerase-utilizing viruses that require a polymerase template switch, characterized as discontinuous transcription, to place a 5?-terminal genomic leader onto subgenomic mRNAs (sgmRNAs). The usually precise switch is thought to occur during the synthesis of negative-strand templates for sgmRNA production and to be directed by heptameric core donor sequences within the genome that match an acceptor core (UCUAAAC in the case of bovine coronavirus) near the 3? end of the 5?-terminal genomic leader. Here it is shown that a 22-nucleotide (nt) donor sequence engineered into a packageable bovine coronavirus defective interfering (DI) RNA and made to match a sequence within the 65-nt virus genomic leader caused a template switch yielding an sgmRNA with only a 33-nt minileader. By changing the donor sequence, acceptor sites between genomic nt 33 and 97 (identical between the DI RNA and the viral genome) could be used to generate sgmRNAs detectable by Northern analysis (?2 to 32 molecules per cell) by 24 h postinfection. Whether the switch was intramolecular only was not determined since a potentially distinguishing acceptor region in the DI RNA rapidly conformed to that in the helper virus genome through a previously described template switch known as leader switching. These results show that crossover acceptor sites for discontinuous transcription (i) need not include the UCUAAAC core and (ii) rest within a surprisingly wide 5?-proximal "hotspot." Overlap of this hotspot with that for leader switching and with elements required for RNA replication suggests that it is part of a larger 5?-proximal multifunctional structure. Copyright © 2006, American Society for Microbiology. All Rights Reserved.
Keywords: Base Sequence; Cell Line; Coronavirus, Bovine; Humans; Models, Molecular; Molecular Sequence Data; Recombination, Genetic; Regulatory Elements, Transcriptional; RNA, Viral; Transcription, Genetic; Virus Replication; Bovine coronavirus; Coronavirus; cis acting element; messenger RNA; nucleotide; oligonucleotide; 5' untranslated region; article; controlled study; Coronavirus; human; Northern blotting; nucleotide sequence; priority journal; replicon; reverse transcription polymerase chain reaction; RNA replication; virus genome; virus transcription